(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1997)
The stratigraphy and age of the S.Cassiano Formation outcropping around the Sella Massif (Dolomites, Northern Italy) were investigated. The unit interfingers with slope deposits pertaining to the Cassian carbonate platform of the Sella Massif. Several stratigraphic sections were analyzed from a sedimentologic and biostratigraphic perspective.Three section (Sella Pass Ia and Ib,Gardena Pass) yielded stratigraphically significant conodont faunas referable to the diebeli Assemblage Zone sensu Krystyn (1983) of latest Ladinian age. Therefore, the Sella Cassian Platform traditionally regarded as a typical Carnian buildup, is also latest Ladinian age. The occurrence of the post-volcanic carbonate platforms older (e.g.Denti di Terra Rossa) and younger (e.g.,the Nuvolau and Lagazuoi platform) than the Sella Platform,suggest that :a) the post-volcanic and Cassian succession of the Dolomites is fare more complex than traditionally thought and b) a sequence stratigraphic model of the Middle-Upper Triassic of the Dolomites based on two generations of Cassian platforms is clearly inadequate to describe the actual succession.